An experimental study of the performance of the solar cell with heat sink cooling system. (April 2019) - Soliman, Aly M.A.; Hassan, Hamdy; Ookawara, Shinichi
Abstract: In the study, an experimental investigation to the performance of the solar cells coupled with heat sink is presented. Indoor experimental setup was designed and assembled to investigate the impact of using heat sink cooling system on the performance of solar cells. Halogen lamps used to simulate the solar radiation and the study is carried out at different solar radiation values. Moreover, the study is carried out at natural and forced air to cool the heat sink. The results show that using heat sink cooling system enhances the performance of the solar cell. Temperature of solar cell decreased by about 5.4 % and 11 % by using heat sink cooling system at natural and forced air over the heat sink, respectively. Moreover, the efficiency and power of the solar cell system increase by about 16 % when heat sink cooling system is used.